Consumer‐grade biosensor validation for examining stress in healthcare professionals. Issue 11 (2nd June 2020) - Hopkins, Luke; Stacey, Benjamin; Robinson, David B. T.; James, Osian P.; Brown, Christopher; Egan, Richard J.; Lewis, Wyn G.; Bailey, Damian M.
Abstract: Introduction: A high prevalence of stress and burnout has been reported among healthcare professionals; however, the current tools utilized to quantify such metrics are not in keeping with doctors' busy lifestyles, and moreover do not comply with infection prevention policies. Given that increased stress can subsequently impact both the healthcare profession and the patient in care, this study aimed to assess the validity of a wearable biosensor to monitor and manage stress experienced by healthcare professionals. Methods: In all, 12 healthy, male volunteers completed an incremental exercise protocol to volitional exhaustion, which aimed to induce physiological stress in a graded manner. A wearable consumer‐grade biosensor (Vital Scout, VivaLNK, Inc.) was used to measure stress, energy expenditure, respiration rate, and activity throughout the exercise protocol. These variables were validated against online breath‐by‐breath analysis (MedGraphics Ultima Series). Results: When compared against online "gold standard" measurements, the Vital Scout biosensor demonstrated a high level of accuracy to measure energy expenditure ( r  = .776, p  < .001) and respiration rate ( r  = .744, p  < .001). The V ˙ O 2 increase observed during the incremental exercise test was associated with the Vital Scout biosensor's measurement of activity ( r  = .777, p  < .001). In contrast, there was a poor relationship between the changes in V ˙ O 2 and the Vital Scout biosensor's ability to detect stress ( r  = −.195, p  = .013). Conclusion: The Vital Scout biosensor provided an accurate assessment of energy expenditure and respiration when compared to the "gold standard" assessment of these parameters. Biosensors have the potential to measure stress and deserve further research in the peri‐hospital environment. Abstract : Increased stress can impact both the healthcare profession and the patient in care, this study aimed to assess the validity of a wearable biosensor to monitor and manage stress experienced by healthcare professionals. A wearable consumer‐grade biosensor was used to measure stress, energy expenditure, respiration rate and activity throughout the exercise protocol. These variables were validated against online breath‐by‐breath analysis. When compared against online 'gold standard' measurements, the biosensor demonstrated a high level of accuracy to measure energy expenditure ( r  = .776, p  < .001) and respiration rate ( r  = .744, p  < .001).